Genotoxicity Assessment of Synthetic Progesterone Hormone (Duphaston) Using Allium cepa Bioassay and RAPD-PCR Technique - Fauzia Elgarabulli; Asma Alilesh (AlQalam Journal of Medical and Applied Sciences, 2026)
Many epidemiological studies have established a strong association between maternal hormonal interventions and the development of abnormalities in progeny, such as inducing autism behavior. In this study, synthetic progesterone genotoxicity was investigated using the Allium cepa assay. The results of treated cells showed a Clastogenic effect, indicating progesterone’s interaction with DNA molecules during cell division (chromosome aberrations), such as anaphase bridges, DNA fragments, and micronuclei. The results also showed cytotoxic action of the synthetic hormone, such as cytomixis, disturbed nuclear membrane, c-metaphase, and early chromosome condensation in prophase. Cell division inhibition at interphase was also observed. The interaction of the widely used synthetic progestrone (Duphaston) in Misurata with DNA was documented by the RAPD technique using random primers. PCR products on gel electrophoresis showed changes in DNA profile, such as band thickness, gain, and loss of bands upon treatment with low (0.025mg/ml) concentration of synthetic progesterone. The chromosomal aberration and changes in DNA profile are evidence of synthetic hormone genotoxicity that may lead to anomalies in the offspring of women who have taken high doses of synthetic progesterone.